Działalność społeczna księdza Antoniego Stychla w Katolickim Towarzystwie Rzemieślników Polskich w Poznaniu w latach 1891-1895 - Taisner, Remigiusz (Ecclesia. Studia z Dziejów Wielkopolski, 2009)
The article presents the activity of Rev. Antoni Stychel in the Catholic Society of Polish Craftsmen and his efforts to unite the Industrial Associations. The Catholic Society of Polish Craftsmen was the first to put into practice the precepts of the encyclical “Rerum novarum”. Earlier, during his studies in Berlin, Rev. Stychel engaged in work on behalf of Polish émigré workers there, also building his experience at social courses which he attended in Germany. He enjoyed great authority in the Society and was awarded the title of its honorary president. Within five years of the Society’s activity the number of its members increased fivefold. Over 100 lectures, prelections and papers were presented to the craftsmen. Events were also organized to foster their cultural and social life.